2020
DOI: 10.1186/s13018-020-01908-y
|View full text |Cite|
|
Sign up to set email alerts
|

In cervical arthroplasty, only prosthesis with flexible biomechanical properties should be used for achieving a near-physiological motion pattern

Abstract: Background In cervical arthroplasty, qualitative motion analysis generally investigates the position of the center of rotation (COR) before and after surgery. But is the pre-op COR suitable as reference? We believe that only a comparison against healthy individuals can answer whether a physiological motion pattern has been achieved. The aim of our study was to examine how the COR for flexion/extension after insertion of 3 biomechanically completely different types of disc prostheses compares to… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…Some have one fixed COR below the motion segment (ProDisc C, DePuy-Synthes; PCM, Cervitech; Discover, DePuy-Synthes), others a COR above the motion segment level with capability for additional sagittal translation (Prestige STLP, Medtronic), again others a variable COR (Bryan, Medtronic) or no articulating surfaces at all but an elastic nucleus (M6, Spinal Kinetics). An analysis of the motion pattern after insertion of a Bryan-, a Prestige STLP or a Discover prosthesis in patients after cervical discectomy could show that a more flexible biomechanical design can contribute to a better physiological motion [1].…”
Section: Introductionmentioning
confidence: 99%
“…Some have one fixed COR below the motion segment (ProDisc C, DePuy-Synthes; PCM, Cervitech; Discover, DePuy-Synthes), others a COR above the motion segment level with capability for additional sagittal translation (Prestige STLP, Medtronic), again others a variable COR (Bryan, Medtronic) or no articulating surfaces at all but an elastic nucleus (M6, Spinal Kinetics). An analysis of the motion pattern after insertion of a Bryan-, a Prestige STLP or a Discover prosthesis in patients after cervical discectomy could show that a more flexible biomechanical design can contribute to a better physiological motion [1].…”
Section: Introductionmentioning
confidence: 99%
“…There are some limitations in this study. First, the location of COR at the level with cervical disc degeneration will change, and the preoperative COR may not represent the physiological COR [45]. Second, our analysis was limited to data collected at two time points: preoperation and the last follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…However, biomechanical characteristics and their influence on clinical outcome have not been assessed thoroughly so far. Muhlbauer et al recommended that only prostheses with flexible biomechanical properties should be used in clinical practice 29 . The MRI assessment showed that progressive degeneration most often occurred at the cranial adjacent segment.…”
Section: Discussionmentioning
confidence: 99%